Assessing Students’ Understanding Towards Critical Reading and Its Impacts Towards Their Lives - rentauli mariah silalahi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2018)
ABSTRACTCritical reading was not a new term for university students but the levels to how students understand it and how it could help them develop in many aspects had seldom been studied. Therefore, this study tried to explore the levels of students’ understanding towards the meaning of critical reading, what possible problems could be present in the implementation, what activities could be carried out for practicing critical reading, and what benefits critical reading could bring to students’ lives. This study; conducted by survey questionnaire, was focused on IT students who had just finished a Reading course and were indicated not in favor of reading. From data analysis, it was found that the IT students did not know well that critical reading required interpreting and criticizing, did not realize potential problems in implementing critical reading and was not aware that critical reading practices could help improve their academic achievements. ABSTRAKMembaca kritis bukanlah sebuah istilah baru untuk mahasiswa tetapi masih jarang dilakukan penelitian terhadap tingkat pemahaman mahasiswa terhadap makna dari membaca kritis dan bagaimana dengan membaca kritis dapat membantu mahasiswa dalam banyak hal. Oleh karena itu, penelitian ini dilakukan untuk melihat tingkat pemahaman mahasiswa terhadap makna membaca kritis, terhadap masalah yang mungkin muncul ketika melakukan kegiatan membaca kritis, terhadap contoh kegiatan yang dapat mengembangkan kegiatan membaca kritis, dan terhadap manfaat dari membaca kritis terhadap kehidupan mahasiswa. Kajian ini, yang dilakukan dengan metode survei kuesioner, difokuskan kepada mahasiswa IT yang baru saja menyelesaikan mata kuliah ‘Membaca’ dan yang diidentifikasi kurang berminat dalam membaca. Dari kajian yang dilakukan ditemukan bahwa mahasiswa IT tersebut tidak mengetahui dengan baik bahwa membaca kritis membutuhkan kemampuan untuk menafsirkan dan mengkritik, tidak menyadari berbagai macam tantangan yang muncul dalam pelaksanaan kegiatan membaca kritis, dan tidak menyadari bahwa dengan membaca kritis mahasiswa dapat meningkatkan prestasi akademik mereka. How to Cite: Silalahi , R. M. (2018). Assessing Students’ Understanding Towards Critical Reading and Its Impacts Towards Their Lives. IJEE (Indonesian Journal of English Education), 5(2), 191-203. doi:10.15408/ijee.v5i2.9532.